Preparation method of pre-lithiation silicon-based composite material, pre-lithiation silicon-based composite material and application thereof

By electrochemically depositing silicon-based composite materials on the surface of lithium rods and carbonizing and sintering at high temperature, the problems of poor consistency and unstable capacity in the preparation of existing prelithiated silicon oxygen materials are solved, and efficient and controllable preparation of prelithiated silicon-based composite materials are achieved, improving the performance of the battery.

CN116062730BActive Publication Date: 2025-03-11SHINGHWA ADVANCED MATERIAL TECH (MEISHAN) CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211483611.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-03-11
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

The existing preparation methods for prelithiated silicon oxygen materials have problems such as poor consistency, difficulty in precise control of prelithium amounts, and capacity instability caused by temperature differences during sintering.

Method used

Li2CO3-coated lithium rods are used as working electrodes, and silicon-based composite materials are deposited on their surface by electrochemical deposition method, and high-temperature carbonization and sintering are carried out to obtain a prelithiated silicon-based composite material.

Benefits of technology

It has achieved the advantages of high silicon deposition density, controllable and stable process, fast time, high lithium replenishment consistency, and high first-time efficiency, avoiding impurities caused by oxidants, and improving rate performance and cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005248414440000091
    Figure GDA0005248414440000091
  • Figure GDA0005248414440000111
    Figure GDA0005248414440000111
Patent Text Reader

Abstract

The invention discloses a preparation method of a pre-lithiation silicon-based composite material, a pre-lithiation silicon-based composite material and an application thereof. A Li2CO3-coated lithium rod is used as a working electrode and a mixed solvent is used as a solvent. A silicon-based composite material is deposited on the surface of the working electrode by an electrochemical deposition method. The silicon-based composite material is subjected to high-temperature carbonization sintering to obtain the pre-lithiation silicon-based composite material. The mixed solvent comprises a silicon-based precursor material and a polymer monomer which are respectively and evenly dispersed in an ionic liquid. The invention has the advantages of high silicon deposition density, controllable and stable process, fast time, high lithium replenishment consistency, etc. The pre-lithiation of the silicon-based material is achieved by a core metal lithium rod. The obtained silicon-based composite material has the characteristics of high initial efficiency, low expansion, etc. Compared with the traditional chemical polymerization method, impurities caused by oxidants are avoided and the reaction efficiency is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion battery preparation, and specifically relates to a method for preparing a pre-lithiated silicon-based composite material. The present invention also relates to the pre-lithiated silicon-based composite material obtained by the preparation method and application thereof. Background Art

[0002] Silicon-based materials are widely used in high specific energy density lithium-ion batteries due to their high energy density and wide range of material sources. Specifically, silicon-based materials usually include two types of materials: silicon-oxygen and silicon-carbon. Silicon-oxygen materials are further divided into first-generation silicon-oxygen, pre-magnesium silicon-oxygen, and pre-lithium silicon-oxygen.

[0003] Pre-lithiated silicon oxide is suitable for high specific energy density lithium-ion batteries with negative electrode specific capacity ≥500mAh / g due to its advantages such as high initial efficiency (90-92%) and high specific capacity (1400mAh / g). At present, the preparation method of pre-lithiated silicon oxide materials on the market mainly adopts the solid phase method, that is, SiO and metallic lithium are sintered in an inert atmosphere, and the pre-lithiated silicon oxide materials are obtained by vapor deposition, but there is poor consistency, the amount of pre-lithiation is difficult to accurately control, and the capacity of the material is different due to the temperature difference in different temperature zones during the sintering process.

[0004] Based on the above situation, the applicant decided to seek technical solutions to solve the above technical problems based on the inventor's many years of dedicated research experience in the fields of silicon-based materials and lithium-ion batteries. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a preparation method of a pre-lithiation silicon-based composite material, a pre-lithiation silicon-based composite material and its application, which has the advantages of high silicon deposition density, controllable and stable process, fast time, high consistency of lithium replenishment, etc. The pre-lithiation of silicon-based materials is achieved through an inner core metal lithium rod, and the obtained silicon-based composite material has the characteristics of high initial efficiency and low expansion; compared with the traditional chemical polymerization method, it avoids impurities caused by oxidants and has high reaction efficiency.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A method for preparing a pre-lithiated silicon-based composite material, using a Li2CO3-coated lithium rod as a working electrode and a mixed solvent as a solvent, depositing a silicon-based composite material on the surface of the working electrode by an electrochemical deposition method; subjecting the silicon-based composite material to high-temperature carbonization sintering to obtain the pre-lithiated silicon-based composite material; wherein the mixed solvent comprises a silicon-based precursor material and a polymer monomer, each of which is uniformly dispersed in an ionic liquid.

[0008] Preferably, the silicon-based precursor material includes one of nano-silicon, SiOx (0<x<2), silicon-aluminum alloy, silicon-copper alloy, silicon-nickel alloy or a mixture of any several of them; and / or the polymer monomer includes one of aniline, thiophene, pyrrole or a mixture of any several of them; and / or the ionic liquid includes one of guanidine hydrochloride, tetramethylguanidine hydrochloride, tetramethyl lactate, tetramethylguanidine hydrogen sulfate or a mixture of any several of them.

[0009] Preferably, the mass ratio of the silicon-based precursor, the ionic liquid and the polymer monomer is 100:100-1000:1-30.

[0010] Preferably, the preparation method of the Li2CO3 coated lithium rod comprises the following steps:

[0011] In an inert atmosphere, a metal lithium sheet is added to an ethylene glycol dimethyl ether solvent to oxidize its surface to generate lithium oxide. In a vacuum environment, carbon dioxide gas is introduced into the solution, and the temperature is increased to allow the carbon dioxide and lithium oxide to react to obtain the Li2CO3 coated lithium rod.

[0012] Preferably, the flow rate of the carbon dioxide is 100-500 ml / min, and the introduction time is not less than 50 min; and / or the pressure of the vacuum environment is -0.9 MPa to -0.1 MPa; and / or the temperature range of the heating is 30-80°C.

[0013] Preferably, in the electrochemical deposition method, the operation steps include:

[0014] The voltage range was -2 V to 2 V and the scan rate was 0.5-5 mV / s for at least 10 cycles.

[0015] Preferably, the high temperature carbonization sintering operation steps include:

[0016] The silicon-based composite material is placed in a carbonization furnace, a carbon source gas is introduced under an inert atmosphere, the temperature is raised to 800-1200° C., and the material is sintered and carbonized for 1-6 hours. After cooling and crushing, the pre-lithiation silicon-based composite material is obtained.

[0017] Preferably, a pre-lithiation silicon-based composite material is prepared by the method for preparing the pre-lithiation silicon-based composite material as described above.

[0018] Preferably, the pre-lithiated silicon-based composite material as described above is used as an active material raw material for preparing a negative electrode plate of a battery.

[0019] Preferably, the battery comprises a lithium-ion battery.

[0020] The present invention uses Li2CO3 coated lithium rods as a matrix and adopts an electrochemical deposition method to obtain a silicon-based composite material, which has the advantages of high silicon deposition density and controllable and stable process. In particular, lithium is supplemented to the silicon-based material by lithium rods, so that lithium supplementation of the silicon-based material from the inner core can be achieved to prepare a pre-lithiated silicon-based composite material, which has technical advantages over the traditional method of using powder mixing for pre-lithiation, such as fast time, high lithium supplementation consistency, and high first-time efficiency. At the same time, the present invention adopts a mixed solvent including a silicon-based precursor material and a polymer monomer to deposit on the surface or inside of the silicon-based material through electrochemical polymerization to obtain an organic polymer (i.e., a silicon-based composite material), and then obtains an amorphous carbon structure through high-temperature carbonization sintering, which can further reduce the electronic impedance of the pre-lithiated silicon-based composite material and improve the rate. In addition, the present invention adopts an electrochemical deposition method, which avoids impurities caused by oxidants compared with traditional chemical polymerization methods, and has high reaction efficiency. DETAILED DESCRIPTION

[0021] The present embodiment discloses a pre-lithiation silicon-based composite material, the preparation method of which adopts a Li2CO3-coated lithium rod as a working electrode and a mixed solvent as a solvent, and deposits a silicon-based composite material on the surface of the working electrode by an electrochemical deposition method; the silicon-based composite material is subjected to high-temperature carbonization sintering to obtain a pre-lithiation silicon-based composite material; wherein the mixed solvent comprises a silicon-based precursor material and a polymer monomer respectively and evenly dispersed in an ionic liquid; preferably, in this embodiment, the mass ratio of the silicon-based precursor, the ionic liquid and the polymer monomer is 100:100-1000:1-30, more preferably 100:100-650:1-20, and further preferably 100:100-500:1-10.

[0022] Preferably, in this embodiment, the silicon-based precursor material includes nano-silicon, SiOx (0<x<2), one of silicon-aluminum alloy, silicon-copper alloy, silicon-nickel alloy or a mixture of any of them; and / or the polymer monomer includes one of aniline, thiophene, pyrrole or a mixture of any of them; and / or the ionic liquid includes one of guanidine hydrochloride, tetramethylguanidine hydrochloride, tetramethyl lactate, tetramethylguanidine hydrogen sulfate or a mixture of any of them. It should be noted that the nano-silicon, SiOx (0<x<2), polymer monomer and ionic liquid used in the implementation of this application can be directly purchased from the market, and the silicon-aluminum alloy, silicon-copper alloy and silicon-nickel alloy can be made by known methods, which will not be specifically described in this embodiment.

[0023] Preferably, in this embodiment, the preparation method of Li2CO3 coated lithium rod comprises the following steps:

[0024] Under an inert atmosphere, a metal lithium sheet is added to an ethylene glycol dimethyl ether solvent to oxidize its surface to generate lithium oxide. In a vacuum environment (preferably at a pressure of -0.9 MPa to -0.1 MPa), carbon dioxide gas is introduced into the solution, and the temperature is raised to 30-80° C. to allow carbon dioxide and lithium oxide to react to obtain a Li2CO3-coated lithium rod. Specifically, preferably, in this step, the flow rate of carbon dioxide is 100-500 ml / min, and the introduction time is not less than 50 min, more preferably 60-480 min.

[0025] Preferably, in this embodiment, in the electrochemical deposition method, the operation steps include:

[0026] In the voltage range of -2V to 2V, the scanning is performed at a scanning speed of 0.5-5mV / s for at least 10 cycles, more preferably 10-100 cycles.

[0027] Preferably, in this embodiment, the high temperature carbonization sintering operation steps include:

[0028] The silicon-based composite material is placed in a carbonization furnace, a carbon source gas is introduced under an inert atmosphere, the temperature is raised to 800-1200° C., and the material is sintered and carbonized for 1-6 hours. After cooling and crushing, a pre-lithiation silicon-based composite material is obtained.

[0029] It should be noted that, when implementing the present application, those skilled in the art may choose to implement it within the above-suggested preferred parameter range (including endpoint values). In order to save the length of the description of the present application, the present application will not elaborate on each one.

[0030] Preferably, the present embodiment also proposes an application of the pre-lithiation silicon-based composite material as described above, and the pre-lithiation silicon-based composite material is used as an active material raw material for preparing battery pole pieces; specifically, it can be used as a battery negative electrode plate, which can be selected according to actual requirements; in the specific implementation, the process for preparing the battery negative electrode plate can adopt any known process, which does not belong to the innovative content of the present application, and the present application does not impose any restrictions on it; it should also be noted that when the present application is implemented, the battery can be a button battery, a soft-pack battery or other well-known batteries, and technical personnel in this field can apply it according to actual needs, and the present application does not impose any special restrictions on this; further preferably, in the present embodiment, the pre-lithiation silicon-based composite material is used as an active material raw material for preparing lithium-ion battery pole pieces.

[0031] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0032] Example 1: Perform the following steps:

[0033] Step S1):

[0034] 100 g of SiOx (purchased directly, specifically selected from SiOx provided by Shanghai Shanshan Technology Co., Ltd., 0<x<2) was added to 300 g of tetramethylguanidine hydrochloride and dispersed evenly, and 5 g of aniline monomer was further added to the tetramethylguanidine hydrochloride and mixed evenly to obtain a mixed solvent A;

[0035] Step S2):

[0036] In an argon inert atmosphere, a metal lithium sheet is added to an ethylene glycol dimethyl ether solvent, and the surface of the metal lithium sheet is oxidized in the ethylene glycol dimethyl ether solvent to obtain lithium oxide; the vacuum degree is evacuated to -0.5Mpa, the temperature is raised to 50°C, and then carbon dioxide gas (flow rate: 300ml / min) is introduced into the ethylene glycol dimethyl ether solvent for 240min, so that carbon dioxide and lithium oxide react to obtain Li2CO3-coated lithium rod B;

[0037] Step S3):

[0038] The Li2CO3-coated lithium rod B obtained in step S2) is used as a working electrode, the mixed solvent A obtained in step S1) is used as a solvent, and saturated calomel is used as a counter electrode. An electrochemical deposition method (i.e., cyclic voltammetry) is used. The voltage range is -2V to 2V, and the scanning speed is 1mV / s for 50 cycles. After that, the working electrode is washed and vacuum dried at 80°C for 24h to obtain a silicon-based composite material C.

[0039] Step S4):

[0040] The silicon-based composite material C is transferred to a tubular furnace (as a carbonization furnace). First, argon inert gas is introduced to expel the air in the tube and methane gas is introduced. Then, the temperature is raised to 900°C for sintering and carbonization for 3 hours. The material is then cooled to room temperature and crushed in an argon inert atmosphere to obtain a pre-lithiation silicon-based composite material.

[0041] The pre-lithiated silicon-oxygen composite material prepared in Example 1 has a granular structure and a uniform size distribution, with a particle size between 5 and 15 μm.

[0042] Example 2: Perform the following steps:

[0043] Step S1):

[0044] 100 g of nano silicon (purchased directly, specifically selected from nano silicon provided by Shanghai Shanshan Technology Co., Ltd.) was added to 300 g of tetramethyl lactate and dispersed evenly, and 1 g of thiophene monomer was further added to the tetramethyl lactate and mixed evenly to obtain a mixed solvent A;

[0045] Step S2):

[0046] Under an argon inert atmosphere, a metal lithium sheet was added to an ethylene glycol dimethyl ether solvent, the vacuum degree was evacuated to -0.1 MPa, the temperature was raised to 30°C, and then carbon dioxide gas (flow rate: 100 ml / min) was introduced into the ethylene glycol dimethyl ether solvent for 480 min to allow carbon dioxide and lithium oxide to react to obtain a Li2CO3-coated lithium rod B;

[0047] Step S3):

[0048] The Li2CO3-coated lithium rod B obtained in step S2) is used as a working electrode, the mixed solvent A obtained in step S1) is used as a solvent, and saturated calomel is used as a counter electrode. An electrochemical deposition method (i.e., cyclic voltammetry) is used. The voltage range is -2V to 2V, and the scanning speed is 0.5mV / s for 10 cycles. After that, the working electrode is washed and vacuum dried at 80°C for 24h to obtain a silicon-based composite material C.

[0049] Step S4):

[0050] The silicon-based composite material C is transferred to a tubular furnace (as a carbonization furnace). First, argon inert gas is introduced to expel the air in the tube and acetylene gas is introduced. Then, the temperature is raised to 800°C for sintering and carbonization for 6 hours. The material is then cooled to room temperature and crushed in an argon inert atmosphere to obtain a pre-lithiation silicon-based composite material.

[0051] Example 3: Perform the following steps:

[0052] Step S1):

[0053] 100 g of silicon-aluminum alloy (90% by weight of silicon and 10% by weight of aluminum, homemade) was added to 500 g of tetramethylguanidine hydrogen sulfate and dispersed evenly, and 10 g of pyrrole monomer was further added to the tetramethylguanidine hydrogen sulfate and mixed evenly to obtain a mixed solvent A;

[0054] Step S2):

[0055] Under an argon inert atmosphere, a metal lithium sheet was added to an ethylene glycol dimethyl ether solvent, the vacuum degree was evacuated to -0.9 MPa, the temperature was raised to 80°C, and then carbon dioxide gas (flow rate: 500 ml / min) was introduced into the ethylene glycol dimethyl ether solvent for 60 min to react with carbon dioxide and lithium oxide to obtain Li2CO3-coated lithium rod B;

[0056] Step S3):

[0057] The Li2CO3-coated lithium rod B obtained in step S2) is used as a working electrode, the mixed solvent A obtained in step S1) is used as a solvent, and saturated calomel is used as a counter electrode. An electrochemical deposition method (i.e., cyclic voltammetry) is used. The voltage range is -2V to 2V, and the scanning speed is 5mV / s for 100 cycles. After that, the working electrode is washed and vacuum dried at 80°C for 24h to obtain a silicon-based composite material C.

[0058] Step S4):

[0059] The silicon-based composite material C is transferred to a tubular furnace (as a carbonization furnace). First, argon inert gas is introduced to expel the air in the tube and ethylene gas is introduced. Then, the temperature is raised to 1200°C for sintering and carbonization for 1 hour. The material is then cooled to room temperature and crushed in an argon inert atmosphere to obtain a pre-lithiation silicon-based composite material.

[0060] Embodiment 4: The technical solution of this embodiment 4 is the same as that of embodiment 3, except that, in this embodiment 4, the silicon-aluminum alloy is replaced by a silicon-copper alloy (90% by weight of silicon and 10% by weight of copper, homemade).

[0061] Embodiment 5: The technical solution of this embodiment 5 is the same as that of embodiment 3, except that, in this embodiment 5, the silicon-aluminum alloy is replaced by a silicon-nickel alloy (90% by weight of silicon and 10% by weight of nickel, homemade).

[0062] In order to verify the technical effects achieved by the embodiments of the present application, the present application also specially sets up the following comparative examples:

[0063] Comparative Example 1: 100gSiO X (Same as SiO in step S1 in Example 1) X ) was ground with 10 g of metallic lithium in an argon atmosphere, and then sintered at 700°C for 1 hour. The temperature was then raised to 900°C, and methane gas was introduced for vapor deposition for 1 hour to obtain a pre-lithiated silicon-oxygen composite material.

[0064] Comparative Example 2: 10 g of the Li2CO3-coated lithium rod B in step S2) of Example 1 was mixed evenly with 100 g of silicon oxide material (purchased from Shanghai Shanshan Technology Co., Ltd.), and 5 g of polyaniline was added and mixed evenly, followed by sintering at 700°C for 1 hour, then heating to 900°C, introducing methane gas, and performing vapor deposition for 1 hour to obtain a pre-lithiated silicon oxide composite material.

[0065] Comparative Example 3: The high first-efficiency pre-lithiation silicon dioxide negative electrode material disclosed in Example 1 of CN112271289A was used.

[0066] Comparative Example 4: The graphene / silane composite material disclosed in Example 1 of CN109546100A was used.

[0067] Comparative Example 5: The rest of the technical solutions of Comparative Example 5 are the same as those of Example 1, except that, in step S1) of Comparative Example 5, 5 g of aniline monomer is not added.

[0068] In order to compare and verify the effects of the above embodiments and comparative examples, the present application uses the silicon-based composite materials obtained in the above embodiments 1-5 and comparative examples 1-5 as active material raw materials for negative electrode materials of lithium-ion batteries, and assembles them by the following method to obtain 10 button batteries, which are respectively recorded as A1, A2, A3, A4, A5, B1, B2, B3, B4, and B5:

[0069] A binder, a conductive agent and a solvent are added to the silicon-based composite materials corresponding to Examples 1-5 and Comparative Examples 1-5, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet, wherein the binder used is LA136D binder, the conductive agent is conductive carbon black (SP), the solvent is double distilled water, and the amount ratio of the silicon-based composite material, SP, LA136D, and double distilled water is 95g:1g:4g:220mL; a metal lithium sheet is used as a counter electrode, a polyethylene (PE), a polypropylene (PP) or a polyethylene propylene (PEP) composite membrane is used as a diaphragm, LiPF6 is used as an electrolyte, and a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 is used as a solvent; and button batteries are assembled in an argon-filled glove box.

[0070] In the present application, the button batteries A1, A2, A3, A4, A5, B1, B2, B3, B4, and B5 prepared in accordance with the above embodiments 1-5 and comparative examples 1-5 were subjected to electrochemical performance tests, respectively. The electrochemical performance tests were specifically carried out on a Wuhan Blue Electric 5V / 10mA battery tester, and the charge and discharge conditions adopted during the test were: the charge and discharge voltage range was 0.005V-2.0V, the charge and discharge rate was 0.1C, and the rate performance (2C / 0.1C) of the button battery was calculated.

[0071] This application conducted a specific surface area test on the silicon-based composite materials corresponding to Examples 1-5 and Comparative Examples 1-5 according to the method of the national standard GB / T 38823-2020 "Silicon Carbon"; the OI values ​​of the silicon-based composite powder materials of Examples 1-5 and Comparative Examples 1-5 were also tested by XRD equipment.

[0072] The above test results are shown in Table 1 below:

[0073] Table 1

[0074]

[0075] It can be seen from the data in Table 1 that the button cells prepared based on the pre-lithiated silicon-oxygen composite materials of Examples 1-5 of the present invention have significantly better discharge capacity and efficiency than those of Comparative Examples 1-5, which proves that the pre-lithiated silicon-oxygen composite materials provided in the present application can enable the battery to have good discharge capacity and efficiency performance; the reason may be that the present invention realizes the pre-lithiation of silicon-oxygen materials by replenishing lithium in the inner core, reduces the irreversible capacity loss of the inner core and improves the initial efficiency, and at the same time, the conductive polymer obtained by the electrochemical deposition method obtains an amorphous carbon structure after carbonization, has good isotropy, significantly reduces the OI value, and further improves the rate performance and cycle performance of the battery to which it is applied.

[0076] In order to compare and verify the effects of the above embodiments and comparative examples, the present application also uses the silicon-based composite materials obtained in the above embodiments 1-5 and comparative examples 1-5 as the active material raw material of the negative electrode material of the lithium ion battery, and assembles them by the following method to obtain 10 soft-pack batteries with a specification of 5Ah. According to the order of embodiments 1-5 and comparative examples 1-5, the corresponding soft-pack batteries prepared are marked as C1, C2, C3, C4, C5 and D1, D2, D3, D4, D5 respectively:

[0077] In the silicon-based composite materials corresponding to Examples 1-5 and Comparative Examples 1-5, 90wt% (percentage by weight of the negative electrode plate) of artificial graphite was doped as the negative electrode material to prepare the negative electrode plate, the ternary material NCM111 was used as the positive electrode material, the Celgard 2400 membrane was used as the separator, LiPF6 was used as the electrolyte, and a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 was used as the solvent, and the concentration of LiPF6 was 1.3 mol / L; a 5Ah soft-pack battery was prepared.

[0078] The present application conducted the following performance tests on the soft-pack batteries prepared in the above Examples 1-5 and Comparative Examples 1-5, respectively. The test results are shown in Table 2 below:

[0079] A. Full power rebound:

[0080] Test method: Measure the thickness D1 of the negative electrode plate in advance; then charge the soft-pack battery to 4.2V, and then use a micrometer to test the thickness D2 of the fully charged negative electrode plate (obtained by dissection), and calculate the full-charge rebound rate of the negative electrode plate. The calculation formula is: Full-charge rebound rate = (D2-D1)*100% / D1.

[0081] B. Cycle test:

[0082] The corresponding test method for soft-pack batteries is: the temperature is set at 25±3℃, the voltage range is set at 2.5-4.2V, the charge and discharge rate is set at 1C / 1C, and the cycle is 500 times.

[0083] C. Ratio test:

[0084] The corresponding soft-pack battery is charged to 4.2V by constant current and constant voltage at a rate of 2C, and then the constant current ratio = constant current capacity / (constant current capacity+constant voltage capacity) is calculated, which is the constant current ratio of the corresponding soft-pack battery.

[0085] Table 2

[0086]

[0087] As can be seen from Table 2 above, the capacity and capacity retention rate of the soft-pack battery prepared by using the pre-lithiation silicon-based composite material obtained in Examples 1-5 after 500 cycles are higher than those of Comparative Examples 1-5. It can be confirmed that the battery prepared by using the pre-lithiation silicon-based composite material of the present invention has good cycle performance and rate performance, and the reason may be that the pre-lithiation silicon-based composite material provided by the present invention deposits the silicon-based composite material on the surface of its lithium rod by electrochemical deposition and coats amorphous carbon, and has the advantages of high silicon deposition density and sufficient pre-lithiation, thereby improving the constant current ratio and cycle performance of the battery to which the silicon-based composite material is applied.

[0088] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0089] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a pre-lithiation silicon-based composite material, characterized in that: A Li2CO3 coated lithium rod is used as a working electrode, a mixed solvent is used as a solvent, and a silicon-based composite material is deposited on the surface of the working electrode by an electrochemical deposition method; the silicon-based composite material is subjected to high-temperature carbonization sintering to obtain the pre-lithiation silicon-based composite material; wherein the mixed solvent comprises a silicon-based precursor material and a polymer monomer which are uniformly dispersed in an ionic liquid; the silicon-based precursor material comprises one or a mixture of any of nano-silicon, SiOx, silicon-aluminum alloy, silicon-copper alloy, and silicon-nickel alloy, and the range of x is: 0<x<2; and / or the polymer monomer comprises one or a mixture of any of aniline, thiophene, and pyrrole; and / or the ionic liquid comprises one or a mixture of any of guanidine hydrochloride, tetramethylguanidine hydrochloride, tetramethyl lactate, and tetramethylguanidine hydrogen sulfate; the mass ratio of the silicon-based precursor, the ionic liquid, and the polymer monomer is 100:100-1000:1-30; the preparation method of the Li2CO3 coated lithium rod comprises the following steps: In an inert atmosphere, a metal lithium sheet is added to an ethylene glycol dimethyl ether solvent to oxidize its surface to generate lithium oxide. In a vacuum environment, carbon dioxide gas is introduced into the solution, and the temperature is increased to allow the carbon dioxide and lithium oxide to react to obtain the Li2CO3 coated lithium rod.

2. The method for preparing the pre-lithiation silicon-based composite material according to claim 1, characterized in that: The flow rate of carbon dioxide is 100-500 ml / min, and the introduction time is not less than 50 min; and / or the pressure of the vacuum environment is -0.9 MPa to -0.1 MPa; and / or the temperature range of the heating is 30-80°C.

3. The method for preparing the pre-lithiation silicon-based composite material according to claim 1, characterized in that: In the electrochemical deposition method, the operation steps include: The voltage range was -2 V to 2 V and the scan rate was 0.5-5 mV / s for at least 10 cycles.

4. The method for preparing the pre-lithiation silicon-based composite material according to claim 1, characterized in that: The high temperature carbonization sintering operation steps include: The silicon-based composite material is placed in a carbonization furnace, a carbon source gas is introduced under an inert atmosphere, and the material is sintered and carbonized for 1-6 hours at a temperature of 800-1200° C. After cooling and crushing, the pre-lithiation silicon-based composite material is obtained.

5. A pre-lithiation silicon-based composite material, characterized in that: The pre-lithiation silicon-based composite material is prepared by the preparation method of any one of claims 1 to 4.

6. An application of the pre-lithiation silicon-based composite material according to claim 5, characterized in that: As the active material raw material for preparing battery negative electrode plates.

7. The use according to claim 6, characterized in that: The battery comprises a lithium ion battery.

Citation Information

Patent Citations

  • Silicon carbon composite film electrode and lithium ion battery

    CN109546100A

  • High-first-effect pre-lithium silicon monoxide anode material and preparation method and application thereof

    CN112271289A

  • Preparation method of silicon-carbon negative electrode composite material

    CN114975946A